Simultaneous Quantification of Plasma Catecholamines and Metanephrines by LC-MS/MS - Dikunets,Marina (2020)
The quantification of the low levels of catecholamines and metanephrines in biological fluids is important for clinical screening of pheochromocytoma/paraganglioma and diagnosis of overtraining syndrome in athletes. We introduce a novel, accurate and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for simultaneous quantification of these biogenic amines in human plasma. Simple protein precipitation combined with rapid 2-aminoethyl diphenylborinate-assisted liquid-liquid extraction allow us to quantify catecholamines and metanephrines over broad concentration ranges. Target analytes were monitored in positive electrospray ionization mode by multiple reaction monitoring. Method performance was validated for linearity, lower limit of quantification, limit of detection, intra-day and inter-assay precision, carry-over, recovery, and matrix effect. The assay was linear within analytical range 25-1000 pg mL-1 for epinephrine, 30-2500 pg mL-1 for norepinephrine, 15-1000 pg mL-1 for dopamine, 25-2000 pg mL-1 for metanephrine and 50-10000 pg mL-1 for normetanephrine, with lower limits of quantification of 15, 20, 10, 15 and 30 pg mL-1, respectively. The intra- and inter-day precisions for all compounds ranged from 0.4 to 6.9% and from 0.9 to 6.6%, respectively. The efficiency of novel method was confirmed by assaying external quality control samples which demonstrated consistent and accurate results.